2021
DOI: 10.1186/s12937-021-00732-2
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity among households with children during the COVID-19 pandemic: results from a study among social media users across the United States

Abstract: Background In the United States, approximately 11% of households were food insecure prior to the COVID-19 pandemic. The present study aims to describe the prevalence of food insecurity among adults and households with children living in the United States during the pandemic. Methods This study utilized social media as a recruitment platform to administer an original online survey on demographics and COVID-related food insecurity. The survey was dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 32 publications
5
61
1
3
Order By: Relevance
“…Although there are many studies that have utilized the USDA food security module in an online format (e.g. 61–63 ), this potentially introduced a barrier for some (though not all) elderly or low-income potential respondents ( 64 , 65 ), as well as those living in rural areas without reliable Internet ( 66 ). Additionally, there have been some studies that show differences in respondent affirmations of food insecurity questions, depending on whether questionnaires are administered online or in person.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many studies that have utilized the USDA food security module in an online format (e.g. 61–63 ), this potentially introduced a barrier for some (though not all) elderly or low-income potential respondents ( 64 , 65 ), as well as those living in rural areas without reliable Internet ( 66 ). Additionally, there have been some studies that show differences in respondent affirmations of food insecurity questions, depending on whether questionnaires are administered online or in person.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic disproportionately impacted these households as they faced challenges related to the closure of schools and childcare centers, in addition to widespread job losses and reductions to job-related income [ 2 , 3 ]. As a result, the prevalence of food insecurity in households with children was higher during the pandemic compared to all households [ 4 ]. Additionally, food insecurity in both households with adults and children has been found to be higher in communities of color due to long-standing structural and systemic inequities [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the prevalence of food insecurity in households with children was higher during the pandemic compared to all households [ 4 ]. Additionally, food insecurity in both households with adults and children has been found to be higher in communities of color due to long-standing structural and systemic inequities [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this research, 41 obese children and adolescents were followed during a three-week shutdown in Verona, with no change in vegetable consumption, and an increase in the consumption of fruit, chips, red meat, and sugar-sweetened beverages; time dedicated to sports activities was reduced by 2.5 h/week and, conversely, time spent sleeping increased by 0.65 h/day; however, the most significant data concerns time dedicated to screen time, which increased by 4.85 h/day [103]. Some studies have observed changes in anthropometric and metabolic parameters that occurred in obese children compared with pre-COVID-19 pandemic [104][105][106][107]. A study conducted on a group of Korean children showed that, within 6 months of social withdrawal and school closure, harmful effects on children's health were already occurring, in particular weight gain, even in normal-weight children, and vitamin D decrease.…”
Section: Pediatric Obesity During the Covid-19 Eramentioning
confidence: 99%